Postoperative recurrence of Crohn's disease: impact of endoscopic monitoring and treatment step‐up. (25th January 2013) - De Cruz, P.; Bernardi, M.‐P.; Kamm, M. A.; Allen, P. B.; Prideaux, L.; Williams, J.; Johnston, M. J.; Keck, J.; Brouwer, R.; Heriot, A.; Woods, R.; Brown, S.; et al.
Abstract Aim Eighty per cent of patients with Crohn's disease require surgery, of whom 70% will require a further operation. Recurrence occurs at the anastomosis. Although often recommended, the impact of postoperative colonoscopy and treatment adjustment is unknown. Method Patients with a bowel resection over a 10‐year period were reviewed and comparison made between those who did and did not have a postoperative colonoscopy within 1 year of surgery, and those who did or did not have a step‐up in drug therapy. Results Of 222 patients operated on, 136 (65 men, mean age 33 years, mean disease duration 8 years, median follow‐up 4 years) were studied. Of 70 patients with and 66 without postoperative colonoscopy, clinical recurrence occurred in 49% and 48% (NS) and further surgery in 9% and 5% (NS). Eighty‐nine per cent of colonoscoped patients had a decision based on the colonoscopic findings: of these, 24% had a step‐up of drug therapy [antibiotics (n = 10), aminosalicylates (n = 2), thiopurine (n = 5), methotrexate (n = 1)] and 76% had no step‐up in drug therapy. In colonoscoped patients clinical recurrence occurred in 9 (60%) of 15 patients with, and 23 (49%) of 47 without step‐up and surgical recurrence in 2 (13%) of 15 and 4 (9%) of 47 (NS). Conclusion Clinical recurrence occurs in a majority of patients soon after surgery. In this cohort, there was no clinical benefit from colonoscopy or increased drug therapy within 1 year after operation. However, the response to the endoscopic findings was not standardized and immunosuppressive therapy was uncommon. Standardizing timing of colonoscopy and drug therapy, including more intense therapy, may improve outcome, although this remains to be proven.